The Effect of Audit Committee, Profitability, Board of Directors on Tax Planning - Samuel, Binsar; Indrati, Menik (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This aim of this research is to analyze the influence of the audit committee, profitability, and the board of directors on tax planning. The research employs three independent variables: audit committee proxied by AC SIZE, Profitability proxied by ROE, and board of direction proxied by DIREKSI. Dependent variabel is measured using the Effective Tax Rate (ETR). A sample of 39 companies from the food and beverage sector was initially selected based on certian criteria, but 10 companies were identified as outlier, leaving 29 companies in the final sample. Consequently, out of a total 117 data observations, only 87 were utilized for analysis. The findings reveal that the audit committee has a positive impact on tax planning, while profitability has a negative impact on tax planning. Additionally, the board of directiors was found to have no significant effect on tax planning. These results provide insights for companies to enhance the effectiveness of their board of directors and strengthen the role of the audit committee in formulating tax planning strategies. The study recommends that stakeholders consider tax governance as a crucial element in evaluating corporate risks. Furthermore, companies should focus on optimizing both efficiency and profitability through balanced tax planning, encuring compliance with tax regulations while promoting long- term sustainability. Ini doing so, companies can improve their credibility with stakeholders and maximize tax benefits to support operational continuity.